The Current Progresses in the Genes and Networks Regulating Cotton Plant Architecture - Huang, Xianzhong; Liu, Hui; Ma, Bin (Frontiers in Plant Science, 2022)
Cotton is the most important source of natural fiber in the world as well as a key source of edible oil. The plant architecture and flowering time in cotton are crucial factors affecting cotton yield and the efficiency of mechanized harvest. In the model plant arabidopsis, the functions of genes related to plant height, inflorescence structure, and flowering time have been well studied. In the model crops, such as tomato and rice, the similar genetic explorations have greatly strengthened the economic benefits of these crops. Plants of the Gossypium genus have the characteristics of perennials with indeterminate growth and the cultivated allotetraploid cottons, G. hirsutum (Upland cotton) and G. barbadense (Sea-island cotton), have complex branching patterns. In this paper, we review the current progresses in the identification of genes affecting cotton architecture and flowering time in the cotton genome and the elucidation of their functional mechanisms associated with branching patterns, branching angle, fruit branch length, and plant height. This review focuses on the following aspects: ⅰ) plant hormone signal transduction pathway; ⅱ) identification of cotton plant architecture QTLs and PEBP gene family members; ⅲ) functions of FT/SFT and SP genes; ⅳ) florigen and anti-florigen systems. We highlight areas that require further research, and should lay the groundwork for the targeted bioengineering of improved cotton cultivars with flowering times, plant architecture, growth habits and yields better suited for modern, mechanized cultivation.